PENGARUH LAYANAN INFORMASI TENTANG KONFLIK INTERPERSONAL TERHADAP KEMAMPUAN PEMECAHAN KONFLIK INTERPERSONAL SISWA KELAS X SMAN 2 SIAKHULU T.P 2014/2015 - Fadella Vioren Y Vioren Y; Raja Arlizon Arlizon; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Information about interpersonal conflict because the importance is given to students at the number of interpersonal conflicts that occur in the school environment. Interpersonal conflict solving ability is the ability, skill and the potential for someone to master all the strategies in resolving interpersonal conflicts. As these strategies is a lose-lose strategy, win-lose strategy and win-win strategy. The purpose of this study is to 1) Knowing picture ability interpersonal conflict resolution before students are given information service on each  strategy. 2) Determine the course of the process of the implementation of information services on the ability interpersonal conflict resolution. 3) Knowing picture ability interpersonal conflict resolution after the given service information on each strategy. 4) Knowing the difference interpersonal conflicts resolution of students before and after the service information on each strategy. 5) Knowing how much influence of information services to on the ability interpersonal conflict resolution on each strategy. This type of research is Pre-Experiment with this type of one-group pre-test and post-test design. The  subjects were students of class X of SMAN 2 Siakhulu which totaled 270 people. Determination of the sample by using simple random sampling and sample in this study as many as 100 people. Data collection method used was a questionnaire. Based on the results of the calculation of the correlation coefficient in a lose-lose strategy obtained r = 0.33 and the coefficient of determination r2 = 0.11, in the win-lose strategy in can be r = 0.46 and r2 = 0.21, and the win-win strategy obtained r = 0.37 and r2 = 0.14. This means contribution information services in a lose-lose strategy of 11%, win-lose strategy of 21% and a win-win strategy of 14%. It can be seen that t count greater than t table, lose-lose strategy (2.083> 1.960), win-lose strategy (4.6> 1.960), and a win-win strategy (8.37> 1.960) so that Ha is accepted. Means that there is influence of information services on the ability of interpersonal conflict resolution class X SMAN 2 Siakhulu TP. 2014/2015. Key Words: information services, interpersonal conflicts student